Association between malnutrition risk and hemorrhagic transformation in patients with acute ischemic stroke - Yuan, Cheng-Xiang; Zhang, Yi-Ni; Chen, Xuan-Yu; Hu, Bei-Lei (Frontiers in Nutrition, 2022)
Background and Aims: Malnutrition is a prevalent problem occurring in different diseases. Hemorrhagic transformation (HT) is a severe complication of acute ischemic stroke (AIS). Few studies have evaluated the association between malnutrition risk and hemorrhagic transformation in patients with acute stroke. We aim to investigate the influence of malnutrition risk on the risk of hemorrhagic transformation in AIS patients. Methods: A total of 182 consecutive adults with HT and 182 age- and sex-matched stroke patients were enrolled in this study. Controlling nutritional status (CONUT) score was calculated to evaluate the malnutrition risk. HT was detected by follow-up imaging assessment, and was radiologically classified as hemorrhagic infarction type 1 or 2 or parenchymal hematoma type 1 or 2. Logistic regression models were conducted when participants were divided into different malnutrition risk groups according to the objective nutritional score to access the risk for HT. Results: The prevalence of moderate to severe malnutrition risk in AIS patients was 12.5% according to CONUT score. Univariate analysis showed that CONUT score is significantly higher in patients with HT than those without HT. After adjusting for potential covariables, the patients with mild risk and moderate to severe malnutrition risk were associated with higher risk of HT compared to the patients in normal nutritional status group (odds ratio, 3.180 [95% CI, 1.139 – 8.874], P = 0.027; odds ratio, 3.960 [95% CI, 1.015 – 15.453], P = 0.048; respectively). Conclusion: Malnutrition risk, measured by CONUT score, was significantly associated with an increased risk of hemorrhagic transformation in patients with AIS.